Pregnancy and Hemodialysis: About a Successful Twin Pregnancy - Medeiros, Rita (2021)
Pregnancy is a rare condition in women with chronic kidney disease on hemodialysis, but its incidence has increased in recent years. Despite being a high-risk condition for both mother and fetus, there has been an improvement in care due to the increased number of cases described and the experience gained in dialysis therapy. We report the case of a multiparous 32-years-old women with chronic hypertension and chronic kidney disease with 10 years of evolution and difficult control, with a diagnosis of dichorionic/diamniotic twin pregnancy, 4 months after beginning hemodialysis. Pregnancy was managed by a multidisciplinary team, hemodialysis sessions were clinically and hemodynamically well tolerated, with good blood pressure and analytical control, as well as adequate development of both fetuses. She went into labor at 34 weeks and 6 days, so a caesarean section was performed, with 2 boys born with adequate weight for gestational age.